IMPROVED STUDENT LEARNING THROUGH MOTIVATIONAL COUNSELING SERVICES GROUP IN SMP MUHAMMADIYAH 28 BARUS ACADEMIC YEAR 2015-2016 - Asmaryadi Asmaryadi (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
The problem in this research is the low student motivation because of the lack of the role of guidance and counseling in schools . In this research to increase student motivation researcher uses group counseling services . This study aims to (1) To determine the increase in student motivation before and after tutoring services group in the experimental group in the Junior Muhammadiayah Barus 28 Academic Year 2015-2016 , (2) To determine the increase in student motivation before and after conventional services on the control group in SMP Muhammadiyah 28 Barus Academic Year 2015-2016. This type of research is true experimental design with shapes pretest- posttest control group design. The study population eighth grade students of SMP Muhammadiyah 28 Barus totaling 2 class . The research sample VIIIA grade students as an experimental class of 10 students and the class as a class VIIIB control as many as 10 students . As a data collection tool is questionnaire . Analysis of the data using the Wilcoxon signed rank test using SPSS version 20.00.  On the results of the hypothesis test score Z for -2.809b with Asymp.Sig ( 2 - tailed) 0.005 ≥ 0.05. And the results of the second hypothesis test score Z for -2.803b with Asymp.Sig ( 2 - tailed) 0.005 ≥ 0.05 so it can be concluded that the first and second hypothesis tested in this study can be accepted , because of the statistical analysis are differences significant in improving students' motivation before and after treatment group counseling services . On average posttest experimental class of 167.1000 while posttest control class is 155.9000.  Based on the above findings, it can be concluded that there is an increase in student motivation through group counseling services in SMP Muhammadiyah 28 Barus Academic Year 2015-2016